Integrated biohydrogen production via lignocellulosic waste: Opportunity, challenges & future prospects - Singh T.; Alhazmi A.; Mohammad A.; Srivastava N.; Haque S.; Sharma S.; Singh R.; Yoon T.; Gupta V.K. (My University, 2025)
Hydrogen production through biological route is the cleanest, renewable and potential way to sustainable energy generation. Productions of hydrogen via dark and photo fermentations are considered to be more sustainable and economical approach over numerous existing biological modes. Nevertheless, both the biological modes suffer from certain limitations like low yield and production rate, and because of these practical implementations are still far away. Therefore, the present review provides an assessment and feasibility of integrated biohydrogen production strategy by combining dark and photo-fermentation as an advanced biochemical processing while using lignocellulosics biomass to improve and accelerate the biohydrogen production technology in a sustainable manner. This review also evaluates practical viability of the integrated approach for biohydrogen production along with the analysis of the key factors which significantly influence to elevate this technology on commercial ground with the implementation of various environment friendly and innovative approaches. © 2021 Elsevier Ltd